2018
DOI: 10.1371/journal.pone.0192492
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two PBO long lasting insecticidal nets against natural populations of Anopheles gambiae s.l. in experimental huts, Kolokopé, Togo

Abstract: LLINs containing an insecticide plus the synergist, piperonyl butoxide (PBO) have been designed for increased efficacy against pyrethroid-resistant malaria vectors. In this study, two LLINs with PBO, PermaNet® 3.0 and Olyset® Plus, and a pyrethroid-only LLIN, Yorkool®, were evaluated in experimental huts against a free-flying, wild population of Anopheles gambiae s.l. in Kolokopé, a cotton cultivated area of Togo. WHO susceptibility tube tests and subsequent molecular assays determine the An. gambiae s.l. popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 19 publications
(21 reference statements)
3
30
0
Order By: Relevance
“…However, next generation LLINs either impregnated with pyrethroids and the synergist PBO or containing chlorfenapyr (Interceptor G2 ® ) are potential alternatives for the improved efficacy of LLINs and for resistance management. Several experimental hut studies have shown improved efficacy of PBO and chlorfenapyr LLINs in controlling pyrethroid resistant malaria vectors compared to conventional pyrethroid LLINs [53][54][55][56][57]. LLINs containing PBO or novel insecticide classes should be considered by the NMCP of DR Congo for future LLIN distribution campaigns in areas of moderate to high intensity of pyrethroid resistance, although the costs of these nets would also need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, next generation LLINs either impregnated with pyrethroids and the synergist PBO or containing chlorfenapyr (Interceptor G2 ® ) are potential alternatives for the improved efficacy of LLINs and for resistance management. Several experimental hut studies have shown improved efficacy of PBO and chlorfenapyr LLINs in controlling pyrethroid resistant malaria vectors compared to conventional pyrethroid LLINs [53][54][55][56][57]. LLINs containing PBO or novel insecticide classes should be considered by the NMCP of DR Congo for future LLIN distribution campaigns in areas of moderate to high intensity of pyrethroid resistance, although the costs of these nets would also need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae s.l. have been conducted in several areas of Togo and showed high level of pyrethroid resistance at Kolokopé (Ketoh et al 2018, Amoudji et al 2019 or surroundings (Djègbè et al 2018). This study reports high pyrethroid intensity resistance in An.…”
Section: Discussionmentioning
confidence: 64%
“…PBO+deltamethrin and PBO+permethrin incorporated, respectively (Ketoh et al 2018). Also, a study by Dadzie et al (2017) in Ghana, reported the role of PBO in enhancing the efficacy of pyrethroid insecticides against An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A practical example of the effect of combining insecticides with synergists, is the increased pyrethroid-susceptibility that was observed when pyrethroids were combined with PBO [23]. In a study by Ketoh et al [233], higher mortality rates and reduced blood-feeding were observed in mosquitoes that were exposed to pyrethroid-treated nets with PBO compared to those exposed to pyrethroid only treated nets. PBO inhibits cytochrome P450 enzymes, which are key players in insecticide resistance, it also increases cuticular penetration of insecticides [233].…”
Section: Combining Insecticide With Synergistsmentioning
confidence: 99%